Opportunities and challenges of converging technology and blended finance for REDD+ implementation - Jang, Eun-Kyung; Kwak, Dongheon; Choi, Gayoung; Moon, Jooyeon (Frontiers in Forests and Global Change, 2023)
The importance of Reducing Emissions from Deforestation and Forest Degradation (REDD+) has been elevated within the new climate framework outlined by the Paris Agreement, placing a significant emphasis on encouraging nations to adopt and promote REDD+ strategies. The success of REDD+ is highly dependent on financial resources that aid in addressing and mitigating the primary causes of deforestation and forest degradation. Furthermore, REDD+ projects utilize technology to counter challenges such as land-use changes for agriculture, infrastructure development, illegal logging, fuelwood collection, and forest fires. This study investigates the status of REDD+ projects, which are aimed at combating global deforestation and climate change, supported by the Climate Technology Center Network (CTCN) and the Green Climate Fund (GCF), both of which are critical mechanisms under the United Nations Framework Convention on Climate Change (UNFCCC). We examined these projects through the lenses of technology convergence and finance blending. The analysis revealed that the CTCN and GCF predominantly support projects leveraging technology for forest disaster management. In addition, the agricultural sector demonstrated the highest degree of technology convergence. The findings indicate that a strategic approach for securing private funding involves integrating mitigation and adaptation efforts in projects. Furthermore, partnerships can facilitate the blending of financial strategies to mitigate risks. The study highlights the potential of technology convergence in enhancing the feasibility of scaling up REDD+ projects by promoting stakeholder engagement and catalyzing the private capital influx.